(3GdChQGb (B((3aj CNHGQ Bd YHGS hCTYGQge(B)s - (3eMeO Hf jMji Hf YHO Gddg, CHh HcQ GdUhdj, hbO jYQa HGdTWQfLj,J (B335 (3g` s
(3ChdgG (B:s
(3CNHGQg (B[(3Cj CHGf(B] (3eY GdQTjO bGd GdUhdj MOKfj eMeO Hf SYjO bGd (B: (3YGJH CHGf GdHQGecI ai EYWGA GdQTjO GdCehGd GdTYQGA s
(3BNQgG (B:s
(3gPG BNQ eG Yedg CHhHcQ GdUhdj ef cJGH GdChQGb , hde jbV dg Cf jYed CNHGQ ESMGb Hf EHQGgje dhaGJg s
(3GfXQ HQbe (B"72" (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B143 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B218 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B57 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs